The KLP+ ("hat") trap, a non-sticky, attractant baited trap of novel design for catching the western corn rootworm (Diabrotiea v. virgifera) and cabbage flea beetles (Phyllotreta spp.) (Coleoptera: Chrysomelidae) - Tóth, M.; Csonka, É.; Szarukán, I.; Vörös, G.; Furlan, L.; Imrei, Z.; Vuts, J. (International Journal of Horticultural Science, 2006)
In the course of research aimed at the development of non-sticky, easy-to-use alternative trap designs for the capture of selected beetle pests, a newly designed "hat" trap, codenamed CSALOMON® KLP+, was compared with conventional trap designs. In the case of the western corn rootworm (WCR) Diabrotica v. virgifera (Coleoptera, Chrysomelidae) the new KLP+ traps baited with pheromonal or floral baits were equally sensitive as the former PAL or PALs sticky "cloak" designs, but the KLP+ traps catch capacity and selectivity was much higher. When baited with the floral WCR bait, the KLP+ trap proved to be more sensitive in capturing female \VCR, than the former sticky PALs trap design.In capturing cabbage flea beetles (Phyllotreta spp., Coleoptera, Chrysomelidae), the new KLP+ trap design baited with allyl isothiocyanate performed better than the previously used VARL+ funnel traps in all respects studied.In conclusion, the new KLP+ trap design, baited with the respective attractants, appears to be advantageous to use for the trapping of both WCR and cabbage flea beetles, and can be recommended for use as a trapping tool in plant protection practice in the detection and monitoring of these pest Coleoptera.